2022
DOI: 10.1259/bjr.20211234
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinically involved lymph nodes with deformable registration in breast cancer radiotherapy

Abstract: Objectives: Modern radiotherapy (RT) techniques require careful delineation of the target. There is no particular RT contouring guideline for patients receiving NACT (neoadjuvant chemotherapy). In this study, we examined the distribution of pre-chemotherapy clinically positive nodal metastases. Methods: We explored the coverage rate of the RTOG breast contouring guideline by deformable fusion of 18-fluorodeoxyglucose positron emission tomography-computed tomography (PET-CT) scan. We retrospectively evaluated n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In this study, 32 out of 142 lymph nodes (23%) were only partially within the radiation field and 9 (6%) were totally uncovered with standard contouring according to the radiation therapy oncology group atlas with CT compared to [ 18 F]FDG-PET. 74 One study evaluating the clinical impact of [ 18 F]FDG-PET and multiparametric MRI in 18 centres in the Netherlands found that the highest impact and observer agreement for disease management was found using these imaging techniques for breast cancer compared to other cancer types, influencing disease management in 96% of all cases. 75 However, it is uncertain how (long-term) outcome such as recurrence- and complication rate is exactly affected by the addition of [ 18 F]FDG-PET, as no prospective comparative studies are available.…”
Section: [ 18 F]fdg-pet In Early Breast Cancermentioning
confidence: 99%
“…In this study, 32 out of 142 lymph nodes (23%) were only partially within the radiation field and 9 (6%) were totally uncovered with standard contouring according to the radiation therapy oncology group atlas with CT compared to [ 18 F]FDG-PET. 74 One study evaluating the clinical impact of [ 18 F]FDG-PET and multiparametric MRI in 18 centres in the Netherlands found that the highest impact and observer agreement for disease management was found using these imaging techniques for breast cancer compared to other cancer types, influencing disease management in 96% of all cases. 75 However, it is uncertain how (long-term) outcome such as recurrence- and complication rate is exactly affected by the addition of [ 18 F]FDG-PET, as no prospective comparative studies are available.…”
Section: [ 18 F]fdg-pet In Early Breast Cancermentioning
confidence: 99%
“…Integrating features and benefits from both modalities, PET/CT dual-modality imaging is consistently growing in part due to its variety of utilities, particularly in RT [9]. Specifically, PET/CT has revolutionized the identification and localization of cancerous lesions (not being able to be identified before the use of PET/CT) and has provided endless medical advances in the realms of not only cancer detection, but also improving the treatment and diagnostic accuracy, prognosis indication, and disease progression and/or response [10,11]. Delineation of tumor margins is an essential first step in the diagnosis and staging of cancerous lesions, and PET/CT has been demonstrated across various studies to improve the accuracy of margin delineation when compared to other image modalities alone [12][13][14][15].…”
Section: Pet/ct Is Changing the Way We Provide CCmentioning
confidence: 99%
“…Compared to either PET or CT alone, PET/CT has also been shown to have a high sensitivity in identifying distant metastases (Table 1) [15][16][17]. The ability to identify distant metastasis more effectively and gauge the size of a tumor using PET/CT has allowed clinicians to more effectively stage cancerous lesions and thus be able to better evaluate a patient's prognosis and devise more effective treatment plans [10,18,19]. More effective cancer staging with PET/CT can also be achieved by evaluating the extent of FDG uptake within the lesion, which varies between tumor subtypes [20][21][22].…”
Section: Pet/ct Is Changing the Way We Provide CCmentioning
confidence: 99%
See 1 more Smart Citation